Persepsi Remaja Muslim Yogyakarta Terhadap Peredaran Hoaks di Media Sosial - Yanti Dwi Astuti; Mustofa Mustofa (Fakultas Dakwah UIN Prof. K.H. Saifuddin Zuhri, 2020)
This research tries to reveal how Muslim teenagers' perceptions and interpretations of hoax news are often circulating in social media. The phenomenon of hoax spreads or false information gets a big moment when social media becomes very common on the internet. People become agents of hoax distribution because they believe in hoax content. Young teenagers are considered the most vulnerable affected by false or hoax news because the characteristics tend to be explorative, always curious, easily influenced, and tend to receive just the contents of the media. It may pose a latent danger and potentially divisive perceptions of society. This research uses Stimulus, Organism, and Response (SOR) theory through qualitative approaches. Data was collected through the FGD method, observation, in-depth interviews, and documentation by using purposive sampling. Meanwhile, to ensure the validity of the data, it is done with the triangulation of data and sources. The results revealed a relationship between understandings of the hoax with the rejection of hoax. It suggests that hoaxes as false news are designed to pose a threat to social life. The study concluded that people, especially Muslim youth, reexamine the truth of the information with